Characteristics Of Herpes Zoster Disease - Nita Ramdhani; Sri Vitayani; Khaeruddin HA (Sean Institute, 2024)
Herpes zoster, or shingles, is a contagious disease caused by the reactivation of the varicella-zoster virus in the body. This virus can become active again when the immune system weakens. Its characteristic symptoms include clustered vesicular rash unilaterally along specific dermatomes, accompanied by radicular pain. Varicella, or chickenpox, is the primary infection that occurs upon initial exposure to the varicella-zoster virus. When the virus reactivates, it causes recurrent infection known as herpes zoster. The risk of developing HZ is influenced by several factors, including age, gender, history of infection, immune status, and comorbidities. This literature aims to explore the characteristics of herpes zoster. The method used is a narrative review of literature. The results obtained in this literature are that there are 15 articles obtained with limitations from 2020 - 2024 and an analysis has been carried out with the limitations of each article regarding the characteristics of herpes zoster disease, 15 articles mention the most dominant characteristics of herpes zoster diseases in this literature review are age (45 -70 years), gender (male), lesion location (thoracic), comorbidities (diabetes mellitus and hypertension), complications (Post Herpetic neuralgia).